Appropriate/Inappropriate: How People Behave Online in Covid-19 Pandemic - Al-Isra, Andi Batara; Rahmi, Ulfiani; Ismail, Ahmad; Saraswati, Andi Irma (Jurnal JINNSA (Jurnal Interdipliner Sosiologi Agama), 2022)
This article discusses how Covid-19 can be categorised as a state of exception, which then changes people's tendency to interact online and how they do it during this pandemic. Interacting online closely relates to people's perceptions of 'being in the world' and how people behave online, i.e. what is considered appropriate and what is considered inappropriate on their 'online interaction'. Using literature review by reading provided materials regarding the topic and drawing some information from our personal experience during the pandemic as additional data, we argue that that Covid-19 announced by WHO as a pandemic is a crisis which caused several countries to declare a 'state of exception'. Thus, policies such as physical distancing change people's tendency to interact, from physical in situ to ‘going online’. People that use various media platforms for interaction can be discussed using the concept of ‘polymedia’, a way of using lots of media interchangeably by considering which one is more appropriate (and inappropriate) for particular situations during the pandemic. It is because polymedia has its own moral dimensions, and it has a relation to how people behave online that is also closely related to the concept of 'ordinary ethics' on their quotidian online interaction.